2009
DOI: 10.1128/aem.01506-08
|View full text |Cite
|
Sign up to set email alerts
|

Bioreduction with Efficient Recycling of NADPH by Coupled Permeabilized Microorganisms

Abstract: The glucose dehydrogenase (GDH) from Bacillus subtilis BGSC 1A1 was cloned and functionally expressed in Escherichia coli BL21(pGDH1) and XL-1 Blue(pGDH1). Controlled permeabilization of recombinant E. coli BL21 and XL-1 Blue with EDTA-toluene under optimized conditions resulted in permeabilized cells with specific activities of 61 and 14 U/g (dry weight) of cells, respectively, for the conversion of NADP ؉ to NADPH upon oxidation of glucose. The permeabilized recombinant strains were more active than permeabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 47 publications
1
37
0
1
Order By: Relevance
“…Due to the high cost of the cofactor, use of the cosubstrate glucose 6-phosphate and lower stability of PICs, strain A is favoured for industrial applications. Zhang et al (2006) increased TTN from 59 to 402 by decreasing cofactor concentration with BpG6PDH regeneration, which is in the same range as our results. A further increase of TTN to more than 4000 was demonstrated by further decreasing the cofactor concentration and simultaneously increasing the cell density, but this led to a loss of activity of 90 %.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Due to the high cost of the cofactor, use of the cosubstrate glucose 6-phosphate and lower stability of PICs, strain A is favoured for industrial applications. Zhang et al (2006) increased TTN from 59 to 402 by decreasing cofactor concentration with BpG6PDH regeneration, which is in the same range as our results. A further increase of TTN to more than 4000 was demonstrated by further decreasing the cofactor concentration and simultaneously increasing the cell density, but this led to a loss of activity of 90 %.…”
Section: Discussionsupporting
confidence: 90%
“…BpG6PDH-coupled regeneration was more efficient than that of BmGDH. External NADP + is necessary for efficient synthesis, if PICs are used, which was also observed by Zhang et al (2006). The lowering of the cofactor concentration from 1 to 0.2 for strain B and to 0.1 for strain A decreased activity to 47 and 48 %, respectively, with simultaneous increase of TTN from 39 to 195 and 391 and almost full conversion of acetophenone, respectively.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It has been demonstrated that about 20% total cellular NAD(H) in wild-type cells is freely accessible and the (4). In several studies, the cellular cofactor concentration has been increased through manipulating the NAD ϩ biosynthetic pathway (12,16) or feeding permeabilized cells (18,36,37). The NAD(H) level was increased up to 6-fold previously (12).…”
Section: Discussionmentioning
confidence: 95%
“…Cofactor recycling plays a key role in the NADPHdependent enzyme biocatalysis; therefore, it is necessary to optimize the reaction condition for proper cofactor recycling [21,22]. To study the effect of cofactor generation, different concentrations of glucose (0.05 to 0.4 M) were used in the reaction mixture.…”
Section: Effect Of Glucose Concentrationmentioning
confidence: 99%